Donor liver quality after hypovolemic shock and venous systemic oxygen persufflation in an experimental animal model - Azin Jafari; Hanno Matthaei; Vittorio Branchi; Edwin Bölke; Rene H. Tolba; Jörg C. Kalff; Steffen Manekeller (European Journal of Medical Research, 2018)
Abstract Background The ever growing demand for liver transplantation inevitably necessitates an expansion of the donor pool. Utilization of “shock organs” is considered suboptimal to date while the associated outcome has hardly been investigated. Materials and methods Male Wistar rats underwent a period of 30 min of hypovolemic shock. After 24 h livers were explanted and prior to reperfusion underwent either 18 h of cold storage (CS; N = 6) or 17 h of CS followed by 60 min venous systemic oxygen persufflation (VSOP; N = 6). The outcome of “shock organs (SHBD)” was compared to heart-beating donor (HBD; N = 12) as positive control and non-heart-beating donor (NHBD; N = 12) as negative control animal groups. Liver function was assessed by measuring enzyme release (AST, ALT, LDH), bile production, portal vein pressure and hepatic oxygen uptake during reperfusion. For reperfusion, the isolated perfused rat liver system was used. Results Liver function was severely limited in NHBD group compared to HBD organs after 18 h of CS (e.g., AST; HBD: 32.25 ± 7.25 U/l vs. NHBD: 790 ± 414.56 U/l; p < 0.005). VSOP improved liver function of NHBD organs significantly (AST; NHBD + VSOP: 333.6 ± 149.1 U/l; p < 0.005). SHBD organs showed a comparable outcome to HBD and clearly better results than NHBD organs after 18 h of CS (AST; SHBD: 76.4 ± 21.9 U/l). After 17 h of CS accompanied by 60 min VSOP, no improvement concerning liver function and integrity of SHBD organs was observed while the results were severely deteriorated by VSOP resulting in higher enzyme release (AST; SHBD + VSOP: 213 ± 61 U/l, p < 0.001), higher portal vein pressure (SHBD: 10.8 ± 1.92 mm Hg vs. SHBD + VSOP: 21.6 ± 8.8 mm Hg; p < 0.05) and lower hepatic oxygen uptake (SHBD: 321.75 ± 3.87 ml/glw/min vs. SHBD + VSOP: 395.8 ± 46.64 ml/glw/min, p < 0.05) at 24 h. Conclusions Our data suggest that the potential of “shock organs” within liver transplantation may be underestimated. If our findings are reproducable in humans, SHBD grafts should be considered as a valuable source for expanding the thus far limited donor pool.